Neighborhood-Level Mass Incarceration and Future Preterm Birth Risk among African American Women - Sealy-Jefferson, Shawnita (J Urban Health, 2020)
While evidence for neighborhood effects on adverse birth outcomes is growing, no studies have examined whether living in a neighborhood impacted by mass incarceration is associated with preterm birth risk. We used modified Poisson regression to test whether residence in a neighborhood impacted by mass incarceration predicted future risk of preterm birth, among African American women. We linked data from the Justice Atlas of Sentencing and Corrections to survey and medical record data from the Life-course Influences on Fetal Environments study (n = 681). We also tested for effect modification by age and marital status. The association between prison admission expenditures and future risk of PTB varied by maternal age at birth, with younger women (< 35) having a modest increase in risk (relative risk (RR) 1.07; 95% confidence interval (CI) 0.99, 1.15), and older (35+ year old) women having lower risk (RR 0.86; 95% CI 0.69, 1.07). The association between the number of prison admissions due to new court cases and future risk of PTB varied by marital status, with evidence that married women may be protected (RR 0.75; 95% CI 0.61, 0.92), while little evidence of association was observed among unmarried women (RR 1.02; 95% CI 0.80, 1.30). The association between residence in an area impacted by mass incarceration and future risk of PTB among African American women may vary by age and marital status. Future research to identify the mechanisms of these associations is warranted.